Basic audiometry learning manual - DeRuiter, Mark; Ramachandran, Virginia (San Diego, CA : Plural Publishing, Inc., 2023)
'Basic Audiometry Learning Manual, Third Edition is designed to provide students and beginning clinicians with instruction in the art and science of clinical audiometry techniques. Well-defined learning outcomes, review of concepts, observation exercises, guided practice, and review materials serve as catalysts for active learning of concepts and provide opportunity for utilization of fundamental audiometry methods. The comprehensive content of the Learning Manual encompasses the breadth of audiologic evaluation, including history taking and patient communication, ear canal assessment and management, immittance, pure-tone testing, masking, speech audiometry, otoacoustic emissions, patient counseling, and report writing'--
Greeting the Patient -- The Patient Interview -- Otoscopic Examination -- Immittance Instrumentation -- Tympanometry -- Acoustic Reflex Thresholds -- Acoustic Reflex Decay -- Audiometer Instrumentation -- Biologic Check of Audiometer Instrumentation -- Obtaining a Threshold -- Obtaining an Unmasked Air-Conduction Audiogram -- Obtaining an Unmasked Bone-Conduction Audiogram -- Masking -- Speech Thresholds -- Word Recognition Testing -- Masking for Speech Audiometry -- The Stenger Test -- Tuning Fork Tests -- Otoacoustic Emissions -- Assessment of Communication Function -- Interpreting Test Results -- Counseling the Patient -- Reporting Results -- Common Pitfalls in Audiologic Evaluation.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 15, 2021).
Added to collection customer.56279.3
Keywords: Audiometry; Audiometry -- methods; Electronic books